PET/CT in Melanoma - Hofman, Michael S.; Hicks, Rodney J. (Clinicians' Guides to Radionuclide Hybrid Imaging, 2017)
This pocket book provides up-to-date guidance on the use of PET/CT in patients with melanoma, which is of rapidly growing importance due to the emergence of immunotherapy. The role of PET/CT in diagnostic workup, staging, treatment selection, prognostication, and follow-up is clearly explained. Imaging features are described and illustrated with the aid of a series of teaching cases, and attention is drawn to normal variants, artifacts, and pitfalls. Readers will also find explanation of the relation of the clinical and pathological background to imaging and the value of PET/CT compared with conventional radiological imaging. The book is published within the Springer series Clinicians' Guides to Radionuclide Hybrid Imaging (compiled under the auspices of the British Nuclear Medicine Society) and will be an excellent asset for referring clinicians, nuclear medicine physicians, radiologists, radiographers, technologists, and nurses who routinely work in nuclear medicine and participate in multidisciplinary meetings.